NILAI-NILAI SUSILA DALAM KITAB CANAKYA NITISASTRA DAN IMPLEMENTASINYA DALAM MEMBENTUK PEMIMPIN YANG BERKARAKTER - Ni Wayan Anggi Yudiantari; I Made Krisna Mahardika; Ni Kadek Ayu Lianita (Guna Widya: Jurnal Pendidikan Hindu, 2025)
Canakya Nītisāstra is a classical Indian literary work that contains moral teachings and ethical values highly relevant to shaping individual character, particularly in leadership. Composed by Rsi Canakya, the text does not solely focus on intellectual intelligence but also emphasizes the importance of moral character, such as honesty, wisdom, self-control, trust, and truthfulness. This study aims to examine the ethical values embedded in Canakya Nītisāstra and their implementation in developing leaders of strong character. The analysis is conducted using a qualitative approach, with literature review as its primary method. It is found that the slokas in this text offer practical guidance for life, including ethical principles, wise decision-making, and a sense of responsibility. These values are further reinforced through the teachings of Seva Niti, which draws inspiration from the traits of animals such as lions, crows, and dogs as symbols of ideal leadership qualities. Moreover, the relevance of these teachings is also reflected in the Hindu leadership philosophy known as Asta Brata. Thus, Canakya Nītisāstra serves not only as a literary heritage but also as a valuable source of ethical and leadership education that remains applicable in contemporary educational and social contexts. This text is worthy of being a reference in shaping a generation of intelligent, ethical, and dharma-grounded leaders.